Passive flow control devices for road vehicles: A comprehensive review - Md. Nazmus Salehin; Nayem Zaman Saimoon; Mim Mashrur Ahmed; Md. Rabiul Islam Sarker; Mahadi Hasan Masud (Engineering Science and Technology, an International Journal)
Aerodynamic drag reduction is considered to be one of the most effective ways to minimize fuel consumption. Hence, this work focuses on reviewing some of the most promising passive flow control techniques for drag and lift reduction in automotive vehicles for enhanced stability and reduced fuel consumption. Firstly, the working physics behind different strategies, like deflectors, diffusers, spoilers, vortex generators, and flaps were elaborately discussed, followed by a detailed comparison among these techniques in terms of resultant drag and lift forces. Among several strategies, the gurney flap showed the huge potential of reducing 67.74% drag force with a slight increase in the lift force. Moreover, straight and concave deflectors can reduce lift force by 118.89% that will improve the aerodynamic stability of the vehicle by a large margin. This study reveals that a combination of a gurney flap, straight-concave deflector, angled fin diffuser, cylindrical vortex generator, and sports wing-lip spoiler is expected to provide the best aerodynamic performance and needs to be further investigated numerically and experimentally. The future scope of the current study is also presented at the end along with the current challenges associated with the implementation of various passive flow control techniques on road vehicles.